Impact of Thermophysical and Biological Pretreatments on Antioxidant Properties and Phenolic Profile of Broccoli Stem Products - Claudia Bas-Bellver; Cristina Barrera; Lucía Seguí (Foods)
Fruit and vegetable industrialisation is a major contributor to food waste; thus, its integral transformation into functional powders has gained attention. Pretreatments can be incorporated into valorisation processes to generate structural or biochemical changes that improve powders’ characteristics. This study deepens into the impact of biological (fermentation, FERM) and thermophysical (autoclaving, AUTO; microwaves, MW; ultrasound, US; and pasteurisation, PAST) pretreatments, combined with dehydration (hot air-drying, HAD; or freeze-drying, FD) on the characteristics of powdered products obtained from broccoli stems. The impact of pretreatments on physicochemical (moisture, water activity, total soluble solids) and antioxidant properties (phenols, flavonoids, antioxidant capacity by ABTS and DPPH) on residue and powdered products was studied, together with their impact on plant tissue structure (Cryo-SEM) and the powders’ phenolic profile (HPLC). Probiotic viability was also determined on the fermented samples. The pretreatments applied, particularly the ultrasound, improved the antioxidant properties of the broccoli stems compared to the unpretreated samples, in line with microscopic observations. Dehydration did also improve the antioxidant attributes of the broccoli wastes, especially drying at 60 °C. However, pretreatments combined with dehydration did not generally lead to an improvement in the antioxidant properties of the powders. Probiotic properties were preserved in the freeze-dried products (>107 CFU/g). In conclusion, pretreatments may be applied to enhance the antioxidant attributes of broccoli wastes, but not necessarily that of dried powdered products.